Social determinants of health disparities in Staten Island compared with Manhattan, Queens, Brooklyn, and the Bronx: Contribution to COVID‐19 outcomes - Masha Kolesnikova; Haram Abdelmajid; Stephan Kohlhoff; Tamar A. Smith‐Norowitz (Immunity, Inflammation and Disease, 2024)
Abstract Introduction Social determinants of health (SDH) negatively affected Coronavirus disease‐2019 (COVID‐19) outcomes within the five boroughs of New York City. The goal of this study was to determine whether differences in social demographics within the borough of Staten Island, compared with the other four boroughs, may have contributed to poor COVID‐19 outcomes in Staten Island. Methods Data were obtained from public data sources. Social demographics obtained included age, household income, poverty status, and education level. COVID‐19 infection, hospitalization, and death rates reported from Staten Island were compared with rates from Manhattan, Queens, Brooklyn, and the Bronx (February 29, 2020–October 31, 2022). Mean differences in case rates of COVID‐19 were higher in Staten Island compared to all four boroughs. Results Mean differences in hospitalization and death rates were higher than Manhattan but similar to the other four boroughs. Within Staten Island, case rates were highest in zip codes 10306 and 10309. Hospitalization and death rates were highest in Staten Island zip code 10304. We found that the zip codes of Staten Island with poorer COVID‐19 outcomes had more individuals with less than a high school degree, lower mean household income, higher proportion of households earning less than $25,000 a year, and a greater proportion of individuals using public transportation. Conclusion Differences in COVID‐19 infection, hospitalization, and death rates exist between the five boroughs and between the 12 zip codes within Staten Island. These differences in COVID‐19 outcomes can be attributed to different SDH.